Efficient electrocatalysts for oxygen evolution. - Lang, Shuang. (2010)
Hydrogen generation by water electrolysis has great potential to be a cost competitive alternative to steam methane reformation or coal gasification production methods, while avoiding emissions of greenhouse gases. However, the kinetics of the oxygen evolution reaction at anode is slow. This project develops anode catalysts with better efficiency by modifying iridium (Ir) with palladium (Pd) at different compositions to promote activity. Synthesis and modification of the catalysts for water electrolysis were developed and tested for the performance of oxygen evolution. Electrochemical tests, namely cyclic voltammetry (CV), chronoamperometry (CA) and X-ray diffraction were performed for the study of the properties of synthesized catalysts. In addition, the effect of different pH values on CV and CA were conducted. Through these electrochemical tests, the electro-catalytic activities of IrO2-PdO at a ratio of 1 to 0.5 were found to be superior to that of pure Ir and pure Pd electro-catalysts. And it also shown that at higher pH values, the catalysts tend to evolve oxygen at a lower voltage and induce a larger electric current value.